2021
DOI: 10.1007/s11606-020-06509-3
|View full text |Cite
|
Sign up to set email alerts
|

Primary Care and Pre-exposure Prophylaxis Services in Publicly Funded Family Planning Clinics in the Southern United States

Abstract: BACKGROUND: HIV pre-exposure prophylaxis (PrEP) is underutilized by US women. Cost and resource concerns are barriers to PrEP delivery in settings that see men. Family planning clinics may be ideal PrEP delivery settings for women, but as they are not uniform in their clinical services, cost and resource concerns may vary. OBJECTIVE: We examined factors that influence perceptions of costs and resources related to PrEP delivery in Title X-funded family planning clinics in Southern states, which overlaps with hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
(16 reference statements)
0
6
0
Order By: Relevance
“…This financial obstacle was corroborated by another study that surveyed clinicians and prescribers in various clinics across the South [17]. They found that prescribers were hesitant to prescribe PrEP due to the perception of PrEP costs and insurance coverage, especially outside of primary care clinics [17].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This financial obstacle was corroborated by another study that surveyed clinicians and prescribers in various clinics across the South [17]. They found that prescribers were hesitant to prescribe PrEP due to the perception of PrEP costs and insurance coverage, especially outside of primary care clinics [17].…”
Section: Discussionmentioning
confidence: 93%
“…For some of the participants, men who have sex with men (MSM), when users are adherent to PrEP in McKenney's study, the authors attributed the low uptake of PrEP in the U.S. due to the financial burden [16]. This financial obstacle was corroborated by another study that surveyed clinicians and prescribers in various clinics across the South [17]. They found that prescribers were hesitant to prescribe PrEP due to the perception of PrEP costs and insurance coverage, especially outside of primary care clinics [17].…”
Section: Discussionmentioning
confidence: 97%
“…Provider and staff knowledge and confidence about PrEP delivery in a family planning setting increased with specific trainings on this topic, but few staff reported having been trained about PrEP screening and delivery [9,22,[37][38][39]. In one study, despite promising results at a 3-month time point, comfort with screening for PrEP eligibility, and physician comfort with prescribing PrEP Provider-level barriers to PrEP care included competing clinical priorities such as time constraints, sensitivity to the emotional needs of patients seeking abortion, and the importance of addressing the patient's primary reason for the visit rather than HIV prevention, insurance-related issues, lack of on-site psychosocial support for risk reduction and adherence counseling, and lack of education materials for patients [2,9].…”
Section: Provider Factorsmentioning
confidence: 99%
“…With nearly 1 million patients a year seeking induced abortion and 1.5 million people attending Title X family planning clinics in 2020 [15,16], and over 90% of women aged 15-44 who had one sexual encounter used some form of effective contraception such as birth control pills, injectable methods, contraceptive patches, or intrauterine devices in their lifetimes [17], this is a way to reach many women. Although family planning clinics offer a unique opportunity for women to receive counseling and PrEP prescriptions [9,13,18,19], implementation barriers include limited knowledge among family planning providers regarding PrEP, worries regarding cost of PrEP, and insurance policies in regards to PrEP [13,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Sales et al applied CFIR to study PrEP implementation in family planning clinics in the Southern United States through an online quantitative survey. 22,23 The CFIR framework is useful to identify and categorize barriers and facilitators that influence implementation outcomes; in this case, Sales et al 23 highlight that outer (availability of resources) and inner setting characteristics (supportive climate of HIV prevention practices and supportive leadership) rather than individual characteristics (knowledge) were the most salient factors associated with readiness to provide PrEP in family planning settings in the Southern United States. Identifying CFIR characteristics that affect PrEP implementation outcomes is vital to improving uptake and persistence among Black cisgender women.…”
Section: Introductionmentioning
confidence: 99%